Bad machinery. Vol. 1, The case of the team spirit - Allison, John, 1976- (Allison, John, 1976- Bad machinery, 2013)
Jack, Sonny, Linton, Shauna, Charlotte, and Mildred-- six kids navigating the treacherous waters of school and adolescence while diving into the whirlpool of mysteries that swirls around the peculiar English town of Tackleford.